DISASTER RISK MANAGEMENT AS A STRATEGIC TOOL FOR BUSINESS RESILIENCE IN SMALL AND MEDIUM ENTERPRISES [MANAJEMEN RISIKO BENCANA SEBAGAI ALAT STRATEGIS DALAM MENINGKATKAN KETAHANAN USAHA PADA USAHA MIKRO, KECIL, DAN MENENGAH] - Rahmat, Hayatul Khairul (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Small and Medium Enterprises play a decisive role in economic development, employment creation, and innovation, yet they remain disproportionately vulnerable to disasters due to limited financial capacity, weak formal governance, and low preparedness levels (Koporcic et al., 2025). The increasing frequency of climate-related hazards, health crises, and supply chain disruptions has transformed disasters into strategic business risks rather than isolated operational events (UNDRR, 2020). Disaster Risk Management has therefore gained prominence not only as an operational safeguard but also as a strategic instrument that enhances organizational resilience and long-term sustainability. This study explores Disaster Risk Management as a strategic tool for strengthening business resilience in Small and Medium Enterprises through an in-depth synthesis of empirical and conceptual literature. Using a qualitative meta-synthesis approach, this research examines how risk identification, preparedness, response, recovery, and adaptive learning collectively shape resilience outcomes in SMEs. The findings demonstrate that SMEs integrating Disaster Risk Management into strategic decision-making exhibit greater adaptive capacity, faster recovery trajectories, and improved business continuity (Sarmiento et al., 2024; Sakijege, 2024). The study contributes to resilience and strategic management literature by repositioning Disaster Risk Management as a dynamic capability that enables SMEs to navigate uncertainty, absorb shocks, and pursue sustainable growth in disaster-prone environments.